Resisting and reinforcing neoliberalism - Luisa Rossini (PlaNext)
In the context of the ongoing global intertwined financial, environmental, socio-political crises, the intricate relationship between neoliberal urban planning and the challenges these crises present has become increasingly visible. Despite these challenges, neoliberal restructuring justifications remain central to urban agendas and planning culture, often exacerbating social inequality. Its principles and related political decisions frequently intensify social conflicts, sparking protests as their adverse effects on marginalized communities and areas become evident, especially after decades of market-driven policies and the global financial crisis. In many cities around the globe, these popular rebellions, as local and residential activism, started increasingly to target varying regulatory regimes and strategies pursued by supranational, national, or local authorities, often organized as urban social movements. This think piece examines how neoliberal urbanism simultaneously incites resistance and absorbs it, reflecting a paradox where insurgent practices challenge the system but are also co-opted into its framework. By exploring key dynamics in urban governance, participation, and social movements, it seeks to understand how neoliberalism’s resilience lies in its ability to incorporate dissent into its operating logic while marginalizing radical alternatives, so to perpetuate its dominance despite widespread opposition. Briefly mentioning some examples of organized groups and forms of resistance around the globe, theoretical debates, and historical perspectives, the discussion unfolds by: analyzing how neoliberal practices shape urban governance and planning; investigating how movements resist neoliberalism and how their ideas are co-opted; addressing the enduring struggle over “to whom the city belongs” and proposing ways to foster meaningful democratic engagement.